2015
DOI: 10.4236/ijohns.2015.42022
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Injections: An Unsolved Mystery

Abstract: Aims: The aim of this study was to test the effectiveness of intratympanic dexamethasone injections as a treatment for severe disabling tinnitus and also observe its effect on hearing loss if any. Materials and Methods: Thirty patients with severe disabling tinnitus in the age group 20 to 60 years were selected and randomly assigned to receive intratympanic injections of a dexamethasone solution 4 mg/ml (0.5 ml) or isotonic saline (0.5 ml) solution under topical anaesthesia, once per week for 4 weeks using a z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Yilmaz et al [18] studied IT dexamethasone injection in 40 patients with nearly the same inclusion and exclusion criteria and reported no significant changes in average high-frequency and SD% and a significant reduction in PTA, which agreed partially with our results. Our results were in agreement with those of Parelkar et al [12], who reported no change in the hearing levels before and after treatment as per the pure-tone audiogram reports in the patient group. Hamid in his study on Meniere's disease noticed a significant gain in speech discrimination (30-60%) that has been associated with IT dexamethasone perfusion.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Yilmaz et al [18] studied IT dexamethasone injection in 40 patients with nearly the same inclusion and exclusion criteria and reported no significant changes in average high-frequency and SD% and a significant reduction in PTA, which agreed partially with our results. Our results were in agreement with those of Parelkar et al [12], who reported no change in the hearing levels before and after treatment as per the pure-tone audiogram reports in the patient group. Hamid in his study on Meniere's disease noticed a significant gain in speech discrimination (30-60%) that has been associated with IT dexamethasone perfusion.…”
Section: Discussionsupporting
confidence: 94%
“…However, Araújo et al [11], in his randomized single-blind study, reported no difference between IT injection of dexamethasone and saline in patients with severe, disabling tinnitus. The same results were reported by Parelkar et al [12] in a recent study.…”
Section: Intratympanic Injection Of Dexamethasone For Controlling Sub...supporting
confidence: 91%
See 1 more Smart Citation
“…The mechanism of action of this therapeutic modality is multifactorial, including antiinformatory effects, a metabolic improving effect, an edema-relieving effect, and suppress the irritated or hypersensitive hair cells in the inner ear, which are believed to cause tinnitus. 10 Pondugula et al pointed at other mechanism of action for IT dexamethazone injection in tinnitus patients, which suggest that steroid perfusion of labyrinthine tissues can affect sodium and fluid transport in vitro studies. 11 The choice of an IT route in the treatment of tinnitus has two advantages: first, high perilymph levels are attained as a result of providing a direct passage through the oval window membrane, and, second, adverse effects of systemic administration of the drug are avoided.…”
Section: Discussionmentioning
confidence: 99%